Merger enforcement in two-sided markets - Przemysław Jeziorski (The Johns Hopkins University, Department of Economics, 2010)
This paper studies mergers in two-sided markets by estimating a structural supply and demand model and performing counterfactual experiments. The analysis is performed on data for a merger wave in U.S. radio that occurred between 1996 and 2006. The paper makes two main contributions. First, I identify the conflicting incentives of merged firms to exercise market power on both sides of the market (listeners and advertisers in the case of radio). Second, I disaggregate the effects of mergers on consumers into changes in product variety and changes in supplied ad quantity. I find that firms have moderate market power over listeners in all markets, extensive market power over advertisers in small markets and no market power over advertisers in large markets. Counterfactuals reveal that extra product variety created by post-merger repositioning increased listeners' welfare by 1.3% and decreased advertisers' welfare by about 160m per-year. However, subsequent changes in supplied ad quantity decreased listener welfare by 0.4% (for a total impact of +0.9%) and advertiser welfare by an additional 140m (for a total impact of -300m).
Keywords: 330